The blue guitar [large type] - Banville, John (Center Point Large Print, 2015)
"As he pushes fifty, painter and petty thief Oliver Otway Orme reflects on his life, trying to uncover the answer to how and why things have turned out as they have, excavating memories of family, of places he has called home, and of the way he has apprehended the world around him"--